2015
DOI: 10.31018/jans.v7i1.599
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Saccharomyces boulardii and Lactobacillus acidophilus fermentation on little millet (Panicum sumatrense)

Abstract: Abstract:The fermentation of little millet (Panicum sumatrense) carried out by probiotic yeast (Saccharomyces boulardii) and lactic acid bacteria (Lactobacillus acidophilus). The germinated little millets grains were fermented for 5 days grains were dried and grounded in a grinder and sieved. The sieved flours were analyzed for proximate composition, minerals and phytic acid content. The results showed that the little millet fermented by combined inoculation of Saccharomyces boulardii and L. acidophilus signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Fermentation by lactic acid bacteria has been shown to reduce tannins and phytic acids and consequently enhance the protein content of finger millet which might be due to the fact that during the lactic fermentation process, the microbial proteolytic enzymes might interfere with indigestible protein‐tannin complexes between the hydroxyl group of tannins and the carbonyl group of proteins (Budhwar et al, 2020). The protein concentration of the microbially fermented little millet varied between 9.86% and 10.95% (Pampangouda et al, 2015). The results of fermented millet flour indicate that L. acidophilus and S. boulardii strains have potentially boosted the protein content and then germinated millet flour, ascertaining that the carbohydrates in the millet flour substrate are destroyed by the strains.…”
Section: Influence Of Processing Methods On Millet Proteins/peptidesmentioning
confidence: 99%
“…Fermentation by lactic acid bacteria has been shown to reduce tannins and phytic acids and consequently enhance the protein content of finger millet which might be due to the fact that during the lactic fermentation process, the microbial proteolytic enzymes might interfere with indigestible protein‐tannin complexes between the hydroxyl group of tannins and the carbonyl group of proteins (Budhwar et al, 2020). The protein concentration of the microbially fermented little millet varied between 9.86% and 10.95% (Pampangouda et al, 2015). The results of fermented millet flour indicate that L. acidophilus and S. boulardii strains have potentially boosted the protein content and then germinated millet flour, ascertaining that the carbohydrates in the millet flour substrate are destroyed by the strains.…”
Section: Influence Of Processing Methods On Millet Proteins/peptidesmentioning
confidence: 99%
“…Only a single cultivation of L. acidophilus increased mineral values of Zn (4.69 mg), Fe (7.98 mg), P (238.43 mg), Mg (141.08 mg), and Ca (41.44 mg). Similarly, both cultures resulted in a significant reduction in phytic acid levels (114.76 mg) compared to the control (188.95 mg) (Pampangouda et al, 2015). Another study examined the effect of microbe combinations (Saccharomyces cerevisiae, Enterococcus faecalis, and Lactobacillus plantarum) as a starter culture on antioxidants and nutritional content in finger millet-horse gram fermented ancient Indian food (dosa).…”
Section: Fermentationmentioning
confidence: 99%
“…Rhizopus azygosporus-assisted fermentation of pearl millet modulates the TPC value of pearl millet from 6.58 to 21.78 mg GAE/g within 10 days [14]. Pampangouda et al [76] reported significant changes after fermentation in different nutrient components of little millet flour. Changes in different components were as follows: 9.8-10.9% (protein), 3.2-2.6% (fat), 39.2-41.4 mg/100g (calcium), 137.6-141 mg/100g (magnesium), 221.4-234.4 mg/100g (phosphorus), 6.6-7.9 mg/100g (iron), 3.8-4.6 mg/100g (zinc) and 188.9-114.7 mg/100g (phytic acid).Omotoke-Azeez et al [11] promulgated the fermentation effect on in vitro digestibility, antioxidant properties and mineral composition of finger millet flour.…”
Section: The Effect Of Ssf On Millet Grainmentioning
confidence: 99%
“…Bioprocessing such as bioleaching/solid-state fermentation has proved its potential to be applicable in the food, feed, chemical and pharma industry for the production of nutrient-rich products with the help of microorganisms [76][77][78]. SSF technology is part of the current trend of research and is widely used by researchers to improve the quality of cereal grains [79].…”
Section: The Effect Of Ssf On Rice Grainmentioning
confidence: 99%